(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Supervision is part of the directing function that plays a role in ensuring that all planned activities are carried out properly. This study aims to determine the effect of supervision on the implementation of the nursing team method at Dr. Pirngadi General Hospital in Medan. The research design used is descriptive correlation, utilizing a questionnaire consisting of 30 statements, divided into 15 questions on supervision and 15 questions on the implementation of the nursing team method. The sample size used in this study is 85 individuals. The results of the Chi-square test showed that df = 4, p = 0.029, which is smaller than the level of significance (α) of 0.05 (p < 0.05) at a 95% confidence level. Based on these results, it can be concluded that there is an influence between supervision and the nursing team method at RUSD Dr. Pirngadi in Medan city